Tomato (Lycopersicon esculentum Mill.) juice restored the number of Leydig cells, and the diameter of the seminiferous tubules of mice (Mus musculus) exposed to lead acetate - Revina Ayu Septiani; Iwan Sahrial Hamid; Emy Koestanti Sabdoningrum; Anwar Ma'ruf; Eka Pramyrtha Hestianah; Maslichah Mafruchati (Ovozoa: Journal of Animal Reproduction, 2022)
Lead is a harmful pollutant from engine exhaust that causes free radicals and has detrimental effects on the testicular tissue. This study aimed to determine the effects of tomato juice on the number of Leydig cells and the diameter of the seminiferous tubules of mice exposed to lead acetate. Twenty-five male mice were divided into five groups. Mice in the control (C-) group were given placebos. Meanwhile, mice in C+, T1, T2, and T3 groups were exposed to lead acetate at a dose of 100 mg/kg BW/day for 14 days and given tomato juice respectively at 0, 0.16, 0.32, and 0.64 mL/day from day 8 to day 35. On day 36, all mice were sacrificed, and the testes were collected for histological preparation. The result showed that lead exposure in the C+ group decreased (p <0.05) in the number of Leydig cells and the diameter of the seminiferous tubules compared to the mice in group C-. Administration of tomato juice in groups T1, T2, and T3 increased (p <0.05) the number of Leydig cells and the diameter of seminiferous tubule compared to the mice in the C+ and C- groups. However, tomato juice administration to the T3 group decreased the number of Leydig cells and the diameter of the seminiferous tubules (p <0.05) compared to the T2 group. In conclusion, an effective dose of 0.32 mL/day of tomato juice restored Leydig cell number and seminiferous tubules diameter in mice exposed to lead acetate.